The Development of Cyberbullying in Social Media Scale - Shabrina Audinia; Dewi Maulina; Riangga Novrianto; Bianca Alia Sudewaji; Izzatullail Arpin Lotusiana (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2023)
Despite the fact that cyberbullying is common on social media, only a few instruments have beendeveloped to assess cyberbullying tendencies in the social media context. The purpose of this study is to develop a Cyberbullying in Social Media Scale (CSMS) for cyberbullying perpetration. Participants are active social media users in Indonesia (n = 958) between the ages of 18 and 40. The Cronbach alpha reliability testing showed that CSMS had a high internal consistency (α =.852). Confirmatory factor analysis revealed that CSMS fit the one-factor model (χ² (54) = 154.891, p < 0.001, RMSEA = 0.044 [90% CI 0.036, 0.052], CFI = 0.906, TLI = 0.885, SRMR = 0.049). Convergent-discriminant validity testing method using the Big Five Inventory also showed that CSMS is valid in measuring cyberbullying perpetration in the social media context. The Cyberbullying in Social Media Scale (CSMS) is a developed unidimensional measurement tool that evaluates cyberbullying tendencies on social media. The CSMS has demonstrated reliability and validity, making it a valuable new instrument for screening and assessing levels of cyberbullying tendencies among young adults in Indonesia. As such, the scale has practical applications for guiding interventions and investigating cyberbullying behavior.